2009
DOI: 10.1128/jvi.01617-08
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus-Mediated Inhibition of Type I Interferon Responses Is a Multifactorial Process Involving the Soluble Type I Interferon Receptor B18 and Intracellular Components

Abstract: Poxviruses such as virulent vaccinia virus (VACV) strain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
70
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 63 publications
8
70
2
Order By: Relevance
“…In addition to MHC molecules, other factors involved in antigen processing, such as TAP and the lysosomal membrane permeabilization components of proteasomes are regulated by IFN. Thus, IFNAR-triggering promotes the switch from proteasome to immuno-proteasome [36,37].In a previous study, we found in an in vitro setting that MVA infection can enhance expression of activation markers and costimulatory molecules on DC, whereas VACV infection effectively inhibited DC activation [16]. Here, we additionally demonstrated that MVA infection induced IFNAR-dependently co-stimulation in vivo that in turn indirectly influenced T-cell priming and expansion of CD8 1 T cells.…”
supporting
confidence: 59%
See 4 more Smart Citations
“…In addition to MHC molecules, other factors involved in antigen processing, such as TAP and the lysosomal membrane permeabilization components of proteasomes are regulated by IFN. Thus, IFNAR-triggering promotes the switch from proteasome to immuno-proteasome [36,37].In a previous study, we found in an in vitro setting that MVA infection can enhance expression of activation markers and costimulatory molecules on DC, whereas VACV infection effectively inhibited DC activation [16]. Here, we additionally demonstrated that MVA infection induced IFNAR-dependently co-stimulation in vivo that in turn indirectly influenced T-cell priming and expansion of CD8 1 T cells.…”
supporting
confidence: 59%
“…VACV deploys a multitude of different strategies to evade immune surveillance. Most notably, VACV efficiently inhibits induction of IFN [15,16], whereas closely related MVA, which was attenuated by more than 570 in vitro passages of chorioallantois vaccinia virus Ankara on chicken embryo fibroblasts, shows several genomic alterations conferring loss of IFN inhibitors [16][17][18].Here, we demonstrate that IFNAR-signaling of T cells critically promotes MVA-induced CD8 1 T-cell proliferation and clonal expansion, whereas upon VACV infection a less stringent correlation was found. MVA-induced T-cell expansion was not associated with a reduced capacity of IFNAR-deficient T cells to get activated but rather with a lack of survival signal.…”
mentioning
confidence: 67%
See 3 more Smart Citations